Collaborative Communication of Jakmania in Mediating Intergroup Conflict - Muhamad Isnaini; Rafif Azmi; Pieter Wilson Loho (ETTISAL : Journal of Communication, 2023)
Intergroup conflict with the manifestation of brawls are a routine occurrence in Johar Baru Sub-District. Efforts to reconcile the warring parties often fail. Alternative mediation actually comes from Jakmania which offers a new narrative to create peace through collaboration with conflicting parties. This study aims to analyze collaborative communication practices in mediating conflicts between street gangs in Johar Baru Sub-District. To answer the research objectives, this study used a qualitative approach with the case study method. Data was collected through in-depth interviews with several informants concerned with peace in Johar Baru Sub-District. The results show that the actors involved in conflict mediation are diverse, including security forces, government officials, community forums, and Jakmania. The deadlock in mediation by the police, RW heads and opinion leaders opened up space for 'fringe' actors, namely Jakmania to mediate, and succeed because peace became more lasting/ maintained. The key to Jakmania's success was the use of collaboration, not contestation. Collaborative communication practices by Jakmania are implemented through the stages of persuasion, dialogue and collaborative communication at the same time. This study concludes that fringe actors such as football club supporter can be alternative mediators in resolving conflicts. This research contributes to: First, the use of collaborative communication as part of strategic communication in communication science. Second, the emergence of alternative actors and their mediation patterns in mediating and resolving similar conflicts elsewhere.